Phloroglucinol-Mediated Hsp70 Production in Crustaceans: Protection against Vibrio parahaemolyticus in Artemia franciscana and Macrobrachium rosenbergii - Kumar, Vikash; Baruah, Kartik; Nguyen, Dung Viet; Smagghe, Guy; Vossen, Els; Bossier, Peter (Frontiers in Immunology, 2018)
The halophilic aquatic bacterium, Vibrio parahaemolyticus is an important aquatic pathogen, also capable of causing acute hepatopancreatic necrosis disease (AHPND) in shrimp resulting in significant economic losses. Therefore, there is an urgent need to develop anti-infective strategies to control AHPND. The gnotobiotic Artemia model is used to establish whether a phenolic compound phloroglucinol is effective against the AHPND strain V. parahaemolyticus MO904. We found that pretreatment with phloroglucinol, at an optimum concentration (30 µM), protects axenic brine shrimp larvae against V. parahaemolyticus infection and induced Hsp70 production (2 folds or more) as compared with the control. We further demonstrated that the Vibrio-protective effect of phloroglucinol was caused by its prooxidant effect and is linked to the induction of Hsp70. In addition, RNAi confirms that phloroglucinol-induced Hsp70 mediates the survival of brine shrimp larvae against V. parahaemolyticus infection. The study was validated in xenic Artemia model and in a Macrobrachium rosenbergii system. Pretreatment of xenic brine shrimp larvae (30 µM) and Macrobrachium larvae (5 µM) with phloroglucinol increases the survival of xenic brine shrimp and Macrobrachium larvae against subsequent V. parahaemolyticus challenge. Taken together, our study provides substantial evidence that the prooxidant activity of phloroglucinol induces Hsp70 production protecting brine shrimp, A. franciscana and freshwater shrimp, M. rosenbergii against the AHPND V. parahaemolyticus strain MO904. Probably phloroglucinol treatment might become part of a holistic strategy to control AHPND in shrimp.